The Complex Interplay of Segmental and Suprasegmental Features in English Phonology: An Advanced Study (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
The study titled "The Complex Interplay of Segmental and Suprasegmental Features in English Phonology: An Advanced Study" delves into the intricate relationships between the segmental (phonemes) and suprasegmental (prosody) elements of English phonology. Utilizing a multifaceted methodological approach, including acoustic analysis, perception experiments, corpus studies, and computer simulations, the research reveals how stress, intonation, and rhythm systematically influence the acoustic properties of vowels and consonants. Acoustic data analysis indicates that stressed syllables have higher pitch, greater intensity, and distinct formant frequencies, enhancing their perceptual salience. Perception experiments demonstrate that listeners heavily rely on prosodic cues to interpret meaning and resolve ambiguities in speech. Corpus studies highlight significant regional and contextual variations in the use of suprasegmental features, underscoring the phonological diversity within English dialects. Computer simulations using autosegmental-metrical models provide a theoretical framework that supports the hierarchical nature of phonological representations, where suprasegmental features modulate segmental structures. Interviews with native speakers and experts emphasize the practical importance of integrating segmental and suprasegmental analyses for comprehensive linguistic understanding and effective communication.